Anisotropic effects of background fields on Born-Infeld electromagnetic waves - Aiello, Matias (2007)
We show exact solutions of the Born–Infeld theory for electromagnetic plane waves propagating in the presence of static background fields. The non-linear character of the Born–Infeld equations generates an interaction between the background and the wave that changes the speed of propagation and adds a longitudinal component to the wave. As a consequence, in a magnetic background the ray direction differs from the propagation direction—a behavior resembling the one of a wave in an anisotropic medium. This feature could open up a way to experimental tests of the Born–Infeld theory.